PENGARUH HASIL BELAJAR BASIC BAKERY PADA KEGIATAN PRAKTIK PASTRY KELAS XI SMK SANDHY PUTRA BANDUNG - Marika Nisvi Setiawan; Sudewi Yogha; Cica Yulia (Universitas Pendidikan Indonesia (UPI), 2016)
Learning Basic Bakery is expected to support the smooth running of the practice , especially in the field of pastry . The purpose of the study were: 1 ) To obtain an overview of the basic learning outcomes bakery 2 ) To obtain an overview of the practical activities choco chip cookies pastry-making with regard to the preparation , implementation and evaluation 3 ) To determine the effect of the learning outcomes of basic bakery pastry practical activities 4 ) To see the influence of the learning outcomes of the activities of the practice of basic bakery pastry - making choco chip cookies . This study used inferential statistical methods . The population is students of class XI fnb management SMK Sandhy Putra Bandung . The sampling technique using random sampling , so the number of respondents as many as 36 people . The results showed the basic learning outcomes included in the criteria sufficiently bakery and pastry practical activities included in the criteria is very competent . Conclusion The study shows that the basic learning outcomes bakery provide a positive and significant effect on the activities of the pastry practices . Suggestions for teachers and schools are basic bakery increase student motivation in carrying out the pastry preparation practices and continue to monitor the students in order to carry out the pastry with a better practice